Peran Mahasiswa KKN dalam Edukasi Anti Bullying: (Studi Kasus di UPT SDN 033915 Pasi) - Rozi Sakhbana Hasibuan; Rahmi Adelia; Juliana Syarah Padang; Annisa Zakia Nasution; Nur Izzaty Rahma; Bhaihaky Alparizky; Nur Anisyah Ritonga; Khalid Samahangga Manik; Rini Sinamo; Sahrul Sahrul (Pusat Riset dan Inovasi Nasional, 2025)
Bullying is one of the issues that frequently occurs in elementary school environments and has serious impacts on children’s psychological, social, and academic development. Efforts to prevent and address bullying are essential through education involving students, teachers, and the surrounding community. This study aims to describe the role of Community Service Program (Kuliah Kerja Nyata, KKN) students in providing anti-bullying education at UPT SDN 033915 Pasi. The research employed a descriptive qualitative method with a case study approach. Data were obtained through observation, simple interviews, and documentation of the anti-bullying seminar activities conducted by KKN students at the school. The results indicate that KKN students act as educators by explaining the definition, forms, and impacts of bullying; as facilitators by creating interactive discussion spaces with students; and as motivators encouraging students to respect one another and reject bullying behavior. Educational strategies were implemented through lectures, discussions, Q&A sessions, and the use of simple visual media. Students’ responses were very positive, demonstrated by their enthusiasm during activities and increased understanding of the dangers of bullying. The study concludes that KKN students play an important role in preventing bullying in elementary schools, while also serving as a tangible contribution of students as agents of social change.